1979
DOI: 10.1111/j.1365-2125.1979.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine and cyclizine alone and in combination on human performance, subjective effects and EEG activity.

Abstract: The effects of caffeine and cyclizine alone and in combination, on performance tests and subjective ratings have been examined in two groups of twelve volunteer subjects using a balanced design for order of administration of treatments, a lactose control and with double-blind conditions. In the second study the electroencephalograph (EEG) was recorded after subjective ratings. Results were analysed by analysis of variance and values of P < 0.05 taken as significant. 2 Caffeine in doses of 75 to 300 mg increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 10 publications
2
56
0
Order By: Relevance
“…For a symbol copying task, however, caffeine alleviated the lorazepam-induced impairment, but had no effect alone (i.e., without lorazepam, there was no difference between the level of performance after caffeine compared with pla cebo). Similarly, cyclizine, an antiemetic agent, was found to significantly impair performance on an arithmetical test, and this was counteracted by 100 mg of caffeine [14]. Interactive effects of this type indicate a net benefit of caf feine irrespective of possible superimposed effects of caf feine withdrawal.…”
Section: Effects Of Caffeine On Deteriorated Performancementioning
confidence: 99%
“…For a symbol copying task, however, caffeine alleviated the lorazepam-induced impairment, but had no effect alone (i.e., without lorazepam, there was no difference between the level of performance after caffeine compared with pla cebo). Similarly, cyclizine, an antiemetic agent, was found to significantly impair performance on an arithmetical test, and this was counteracted by 100 mg of caffeine [14]. Interactive effects of this type indicate a net benefit of caf feine irrespective of possible superimposed effects of caf feine withdrawal.…”
Section: Effects Of Caffeine On Deteriorated Performancementioning
confidence: 99%
“…A typical procedure is to compare the effects of caffeine and a placebo in caffeine-deprived subjects (e.g. Clubley et al 1979;Bruce et al 1986;Lieberman et al 1987). The problem with this approach is that it leaves open the question as to whether the findings are due to beneficial effects of caffeine or to deleterious effects of caffeine deprivation (or a combination of both of these).…”
Section: Alcohol and Caffeinementioning
confidence: 99%
“…In the delta bandwidth, broadly defined as 0-4 Hz, caffeine has been reported to increase [7] , decrease [8][9][10][11] , and to have no effect [12][13][14][15][16] on EEG power within that band. In the theta bandwidth, broadly defined as 4-8 Hz, caffeine has been reported to decrease theta power [8,10,11] and to have no effect [7,[12][13][14][15][16] .…”
mentioning
confidence: 99%
“…In the delta bandwidth, broadly defined as 0-4 Hz, caffeine has been reported to increase [7] , decrease [8][9][10][11] , and to have no effect [12][13][14][15][16] on EEG power within that band. In the theta bandwidth, broadly defined as 4-8 Hz, caffeine has been reported to decrease theta power [8,10,11] and to have no effect [7,[12][13][14][15][16] . Several studies have reported caffeine-induced decreases in the alpha bandwidth, broadly defined as [8][9][10][11][12] Hz [8][9][10][15][16][17][18][19] , but an increase has also been reported [11] , as has no effect [7,12,13] .…”
mentioning
confidence: 99%